Inclusive seed systems for better nutrition and sustainable food systems in Mali - Sylla, Almamy; Kasala, Kavitha; Ravula, Padmaja; Afari-Sefa, Victor; Cissé, Boubakary; Sidibé, Mamourou; Jumbo, McDonald Bright (Frontiers in Nutrition, 2025)
Women are central to agricultural production in Mali, yet systemic barriers limit their participation in inclusive seed systems and resilient food systems. In seed systems, restricted access to high-quality seeds, financial constraints, and limited technical training hinder women’s engagement in formal seed production and distribution. Within food systems, weak market integration, inadequate mechanization, and insufficient processing infrastructure constrain their ability to transform biofortified crops into value-added food products. Addressing these challenges requires a holistic, gender-responsive approach that strengthens women’s roles across the seed-to-nutrition pathway. This perspective article synthesizes insights from two key initiatives: The Networking for Seed Project-Phase II, which enhances community seed systems by promoting women’s participation in seed production and dissemination, and a pilot initiative by the World Food Program, which facilitates the processing, commercialization, and market integration of biofortified crops. These initiatives highlight the importance of linking seed systems with food processing and market access to create economic opportunities for women while improving household and community nutrition. By enhancing financial inclusion, utilizing technological tools, and strengthening institutional support, these approaches help women shift from being passive recipients of agricultural inputs to becoming active and empowered entrepreneurs. Integrating women more effectively into both seed and food systems contributes to more sustainable and equitable agricultural value chains, strengthening food security, nutrition outcomes, and climate resilience in Mali.